Chemical derivatization of pharmaceutical samples prior to Gas-Chromatography and Mass-Spectrometry analysis - Bajpai, Vivek K.; Kim, Na-Hyung; Kim, Kangmin (Bangladesh Journal of Pharmacology, 2016)
Derivatization is the process by which a compound is chemically changed, that has properties more amenable to a particular analytical method. Some samples analyzed by Gas-chromatography and Mass-spectrometry (GC-MS) require derivatization in order to make them suitable for analysis. Especially the compounds that have poor volatility, poor thermal stability, or that can be adsorbed in the injector will exhibit non-reproducible peak areas, heights, and shapes. Hence, this study focused on step-by-step visual demonstration of chemical derivatization of pharmaceutical samples prior to GC-MS analysis for their better elution and detection. Video Clip of Methodology: Part 1: 5 min 8 sec Full Screen Alternate Part 2: 6 min 13 sec Full Screen Alternate Part 3: 53 sec Full Screen Alternate